Variation in instructive style in Prophet Muhammad's discourses: an analytical study in light of modern socio-linguistics - Wan Sulong, Wan Muhammad; Yeob, Shamsul Jamili (International Islamic University Malaysia Press, 2013)
Prophet Muhammad’s (peace be upon him) discourses are a rich source and mine of knowledge and edifying instruction, and are an important part of the Prophetic Traditions which constitute the second source of Islamic teachings next to the Qur’an. The Prophetic discourses have been recorded and transmitted with a very degree of preciseness in both letter and content. Thus they provide a great record and comprehensive register of social life during the Prophetic era. In view of this, the present article aims at discovering the elements and aspects of that social life by identifying and examining the linguistic forms and speech modes employed in the Prophetic discourses and discerning their relationships with the socio-cultural context prevailing during the occurrence of the Prophet’s speech acts. No doubt, in carrying out his prophetic mission to convey God’s message to people, the Prophet (peace be upon him) made use of all that was available to him in terms of the Arabic language’s stock of speech styles, modes of expression and ways of linguistic performance. It is a characteristic feature of his discourses that his speech would be commensurate with the requirements of the actual situation. Thus, he was always keen to address each group of people, indeed each individual, according to their level and standing and to make his speech relevant to the situation. Therefore, the article focuses on the styles of speech in the Prophetic discourses meant for edifying people and directing them to perform certain actions. This task has been done by analyzing three speech acts of the Prophet recorded in Sahih Muslim, in which exercise the author has had recourse to American linguist Dell Hymes’ model of determining the components of a speech act or speech event which he summarized in the expression SPEAKING whereby each letter conforms to first letter of the name of each of those eight components taken as criteria for discovering and assessing the relationship between speech modes and the context.